An unmanned aerial vehicle (UAV) technology for estimating leaf N content in rice crops, from multispectral imagery - CGIAR Research Program on Rice (2020)
Proof of concept delivered. Three machine learning methods based on multivariable linear regressions (MLR), support vector machines (SVM), and neural networks (NN), were applied and compared through the entire phonological cycle of the crop: vegetative (V), reproductive (R), and ripening (Ri).